Patient-reported pain and other symptoms among breast cancer survivors: prevalence and risk factors. Issue 6 (December 2020) - Divella, Michele; Vetrugno, Luigi; Bertozzi, Serena; Seriau, Luca; Cedolini, Carla; Bove, Tiziana
Objective: To investigate the prevalence and risk factors associated with chronic pain and other symptoms related to breast cancer 6 months after surgery. Methods: In an observational study of 261 female breast cancer survivors treated between January 2017 and January 2018, patients were asked about their pain symptoms using a questionnaire that utilized the Numeric Rating Score (NRS) and the Douleur Neuropathique Score (DN4) for neuropathic pain; it also addressed phantom sensations and functional disorders on the ipsilateral shoulder. A total of 218 women completed the survey. Results: A total of 105 patients (48.17%) reported chronic pain. Of these, 64% rated the pain with an NRS of 1–3 and 35% with an NRS >3. Neuropathic pain was reported in 65% of the sample, phantom sensations in 12%, disorders of shoulder function in 16%, and web syndrome in 2%. Multivariable analyses showed that chronic pain (odds ratio [OR], 2.55; 95% confidence interval [CI], 1.094–5.942; p < 0.05) and neuropathic pain (OR, 2.988; 95% CI, 1.366–6.537; p < 0.05) were positively associated with surgical adverse events; phantom sensations were statistically associated with the weight of removed breast tissue (OR, 1.003; 95% CI, 1.001–1.005; p < 0.05). Conclusions: Our study highlights the need to employ specific tools capable of detecting different kinds of chronic pain after breast cancer surgery to improve pain prevention and treatment. Surgical complications and the weight of removed breast tissue emerged as 2 of the risk factors for chronic and neuropathic pain development in breast cancer survivors.